Plan estratégico de marketing para el “HOTEL CIUDAD DE CATAMAYO” del cantón Catamayo provincia de Loja, periodo 2017-2020 - Sánchez Balcázar, Erika Germania (2018)
The present thesis has as purpose is to prepare a Strategic Marketing Plan for the Hotel Ciudad de Catamayo del Cantón Catamayo, province of Loja. Currently, it has commercial problems such as the decrease of its income, this is due to the fact that there is a low level of seasonality of customers, due to the existence of competition, and that marketing strategies are not established; and as well as the limited publicity campaign, that is why the need to elaborate this plan is created, which helps to create strategies that allow to stand out against the competition. The present work has as objective to make a current situational diagnosis in which it includes evaluating and analyzing the external factors, the competitive factors and internal factors that affect the development of the organization; and make the proposal of strategic marketing plan for the hotel that will allow to attract more customers, improve their competitiveness and increase their income. For the development and execution of this work was necessary to use three methods: the deductive, inductive and historical, within the techniques that were used for data collection were: direct observation through visits to the hotel, the interview that was made the owner manager and the survey that were applied to tourists, through which it was possible to obtain relevant and current information about the Hotel Ciudad de Catamayo. Then we proceed to perform the external analysis in which the factors were analyzed: Political, Economic, Social, Technological and Cultural, determining their opportunities and threats; what allowed to make the matrix of external factors (EFE), obtaining a total of 2.92 which means that the strategies used by the organization allow to take advantage of existing opportunities and minimize their threats affecting the hotel, likewise proceeded to perform the competitive analysis, through the five forces of Porter, then the matrix of competitive profile was made determining as direct competition according to its category to the Hotel MarcJon's where the hotel Ciudad de Catamayo is in 5 second place with a weighted total of 3.13, and first of all is the Marcjon's hotel with a total of 3.33, therefore strategies should be developed to make the hotel more known by implementing more publicity and taking advantage of its most important factors. An internal analysis was also carried out, for which an interview was applied to the hotel's owner manager, who helped us to prepare the matrix EFI obtains a weighted total of 2.74, which indicates that the organization is slightly stronger than weak After the internal and external factors were determined and analyzed, the SWOT matrix was prepared. Based on all the analyzes established, the strategic marketing plan proposal was made with the purpose of leading the company for improvement, which contains four strategic objectives which are: 1. Carry out a promotion plan to give know the services offered by the "Ciudad de Catamayo" hotel. 2. Implement the after-sales service to improve the quality of service at the Ciudad de Catamayo hotel. 3. Improve market participation by establishing strategic alliances with public and private institutions. 4. Implement a software system to improve the administrative management of the hotel, resulting in a total budget of $ 5,018.35. Finally, it concludes with conclusions, the same ones that are aimed at fulfilling the objectives of the project; and the recommendations where the manager of the Ciudad de Catamayo Hotel is proposed to develop a strategic marketing plan to increase their market share and increase their revenues.